2019
DOI: 10.1038/s41598-019-56088-5
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical response of Rhodotorula mucilaginosa and Cladosporium herbarum isolated from aquatic environment on iron(III) ions

Abstract: The objective of the paper was to determine the influence of iron(III) ions on the growth and metabolism of fungi commonly occurring in waters: the yeast Rhodotorula mucilaginosa and filamentous fungus Cladosporium herbarum. Cells of R. mucilaginosa were shown to absorb the most iron(III) ions at a concentration of 1 mg/L iron(III) ions. Yeast cells showed a considerable increase in the content of proteins and monosaccharides, as well as biomass growth. At higher concentrations of iron(III) ions, the yeast lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Rhodotorula is a genus of eukaryotic microorganisms in the family Sporidiobolaceae (order Sporidiales , class Pucciniomycetes , phylum Basidiomycota ) that is widely found in animals, plants, rivers, lakes, and oceans (Falces-Romero et al, 2016 ; Cudowski and Pietryczuk, 2019 ; Daudu et al, 2020 ). Cells of Rhodotorula not only are rich in conventional nutrients such as carotenoids, proteins, and polysaccharides but also contain amino acids, polyunsaturated fatty acids, vitamin E, nucleotides, and astaxanthin (Gupta et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Rhodotorula is a genus of eukaryotic microorganisms in the family Sporidiobolaceae (order Sporidiales , class Pucciniomycetes , phylum Basidiomycota ) that is widely found in animals, plants, rivers, lakes, and oceans (Falces-Romero et al, 2016 ; Cudowski and Pietryczuk, 2019 ; Daudu et al, 2020 ). Cells of Rhodotorula not only are rich in conventional nutrients such as carotenoids, proteins, and polysaccharides but also contain amino acids, polyunsaturated fatty acids, vitamin E, nucleotides, and astaxanthin (Gupta et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence has shown that the genus Cladosporium has a relatively strong broad-spectrum tolerance to HMs such as Cu, Hg, Al, Au, Ag, Cd, and Fe (Cudowski & Pietryczuk, 2019;V acar et al, 2021). However, the tolerance of Cladosporium to As has rarely been reported.…”
Section: Discussionmentioning
confidence: 99%
“…mucilaginosa was observed that iron (III) ions in yeast cells was improved 9-fold in comparison to the control under the influence of 1 mg/L iron (III) ions and 11-fold under the influence of 100 mg/L and showed no decrease in the R . mucilaginosa biomass at high concentrations of iron (III) ions in the medium ( Cudowski and Pietryczuk, 2019 ). Aibeche et al.…”
Section: Beneficial Effect Of R Mucilaginosa On Pl...mentioning
confidence: 99%
“…(2022) CGMCC-16597 Biosorption Lead (Pb) Removal Wang et al. (2021) - Biosorption Iron (III) (Fe) Removal Cudowski (2019) R1 Bioremediation Hydrargyrum (Hg) Removal Liu et al. (2017) CCMB 604 Enzyme producing Inulinase da Silva et al.…”
Section: Beneficial Effect Of R Mucilaginosa On Pl...mentioning
confidence: 99%